(untitled) (AYUSHDHARA, 2024)
Shwasa Roga is a disease of Pranavaha Srotas. Ayurvedic literature reveals that Prana Vayu in its physiological form is responsible for normal respiration. But when vitiated Vata predominately Prana Vayu is obstructed by Kapha and moves in opposite direction (upward) then it leads to Shwasa Roga. COPD is difficult to treat due to pulmonary as well as systemic involvement and its fatal complications. There is a need for disease prevention and disease management initiatives. It affects the individual physically, socially, financially and even emotionally. So there is need to explore and establish an effective treatment module having least or no side effects with evident therapeutic potential. This study was conducted to find out an effective drug therapy for the management of this disease with least or no side effects. The trial was done on 30 registered patients who were diagnosed with Shwasa Roga w.s.r to COPD and were randomly divided in two groups, consisting 15 patients in each group. Bharangyadi Kwatha and Kaliphala (Vibhitak) Churna were the trial drugs, whereas Doxofylline was the standard drug. 15 patients of group I were given Bharangyadi Kwatha in the dose of 25ml twice a day and Kaliphala Churna in the dose of 5gm twice a day with Madhu. 15 patients of control group were given Tab. Doxofylline 400mg once a day. Assessment of various subjective and objective parameters was done before and after the trial. Obtained data was tabulated and statistically analysed.